Methylobacterium ajmalii sp. nov., Isolated From the International Space Station - Bijlani, Swati; Singh, Nitin K.; Eedara, V. V. Ramprasad; Podile, Appa Rao; Mason, Christopher E.; Wang, Clay C. C.; Venkateswaran, Kasthuri (Frontiers in Microbiology, 2021)
Four strains belonging to the family of Methylobacteriaceae were isolated from different locations on the International Space Station (ISS) across two consecutive flights. Of these, three were identified as Gram-negative, rod-shaped, catalase-positive, oxidase-positive, motile bacteria, designated as IF7SW-B2T, IIF1SW-B5, and IIF4SW-B5, whereas the fourth was identified as Methylorubrum rhodesianum. The sequence similarity of these three ISS strains, designated as IF7SW-B2T, IIF1SW-B5, and IIF4SW-B5, was <99.4% for 16S rRNA genes and <97.3% for gyrB gene, with the closest being Methylobacterium indicum SE2.11T. Furthermore, the multi-locus sequence analysis placed these three ISS strains in the same clade of M. indicum. The average nucleotide identity (ANI) values of these three ISS strains were <93% and digital DNA-DNA hybridization (dDDH) values were <46.4% with any described Methylobacterium species. Based on the ANI and dDDH analyses, these three ISS strains were considered as novel species belonging to the genus Methylobacterium. The three ISS strains showed 100% ANI similarity and dDDH values with each other, indicating that these three ISS strains, isolated during various flights and at different locations, belong to the same species. These three ISS strains were found to grow optimally at temperatures from 25°C to 30°C, pH 6.0 to 8.0, and NaCl 0 to 1%. Phenotypically, these three ISS strains resemble M. aquaticum and M. terrae since they assimilate similar sugars as sole carbon substrate when compared to other Methylobacterium species. Fatty acid analysis showed that the major fatty acid produced by the ISS strains are C18:1- ω7c and C18:1- ω6c. The predominant quinone was ubiquinone 10, and the major polar lipids were diphosphatidylglycerol, phosphatidylcholine, phosphatidylethanolamine, phosphatidylglycerol, and an unidentified lipid. Therefore, based on genomic, phylogenetic, biochemical, and fatty acid analyses, strains IF7SW-B2T, IIF1SW-B5, and IIF4SW-B5, are assigned to a novel species within the genus Methylobacterium, and the name Methylobacterium ajmalii sp. nov. is proposed. The type strain is IF7SW-B2T (NRRL B-65601TT and LMG 32165T).